Direct and inverse problems for the Dirac operator with a spectral parameter linearly contained in a boundary condition - Amirov, R. Kh.; Keskin, B.; Özkan, G. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate a problem for the Dirac differential operators in the case where an eigenparameter not only appears in the differential equation but is also linearly contained in a boundary condition. We prove uniqueness theorems for the inverse spectral problem with known collection of eigenvalues and normalizing constants or two spectra.